Osteotomy About the Knee A Comprehensive Guide - Oussedik, Sam.; Lustig, Sebastien; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Degenerative conditions of the knee place an increasing burden on health economies and lead to pain and functional loss for sufferers. Although arthroplasty may not offer a level of functional restoration that meets all patients$1 (Bexpectations, joint preservation through osteotomy is a viable option in younger, more physically active patients. This volume is a comprehensive technical guide to performing knee-preserving surgery to treat degenerative conditions and malalignment-associated knee instability. Drawing on their extensive experience of these procedures, the authors provide valuable insights into identifying patients who may benefit, as well as planning and performing the procedures with a high degree of precision, and explaining the results that can be achieved. This book both initiates novices and provides technical tips for experienced surgeons, and as such is an indispensible resource for all clinicians who treat patients with knee conditions.s
Part 1. Basic science -- From Hippocrates to Coventry and beyond - the history of joint realignment -- Load, alignment and wear -- Principles of alignment correction surgery -- Part II. Realignment surgery (HTO/DFO) -- Outcomes of surgery for medial arthrosis -- Outcomes of surgery for lateral arthrosis -- Outcomes of surgery for sagittal instability -- Outcomes of surgery for coronal instability -- Part III. Surgical technique -- Medial opening wedge high tibial osteotomy -- Lateral closing wedge high tibial osteotomy -- Lateral opening wedge distal femoral osteotomy -- Medial closing wedge distal femoral osteotomy -- Lateral opening wedge high tibial osteotomy -- Medial closing wedge high tibial osteotomy -- Sagittal plane correction -- PSI for High Tibial HTO -- Navigation for HTO -- Part IV. Revision surgery -- Indications and Outcomes of revision to another HTO -- Revision to TKR -- Outcomes of Total Knee Arthroplasty for failed osteotomy.
Keywords: Orthopedics; Sports medicine; Rheumatology; Surgical Orthopedics; Sports Medicine; Rheumatology